Rapid assessment of direct oral anticoagulants in acute stroke: an educational systematic review - Mbroh, Joshua; Birschmann, Ingvild; Ebner, Matthias; Kremer Hovinga, Johanna A.; Lindhoff-Last, Edelgard; Purrucker, Jan; Schäfer, Simon T.; Tünnerhoff, Johannes; Wang, Yi; Poli, Sven (European stroke journal, 2025)
Purpose: To provide an overview on commercially available point-of-care tests (POCT) for rapid assessment of direct oral anticoagulant (DOAC) activity, their diagnostic accuracy in identifying blood samples containing clinically relevant DOAC concentrations, and guidance on selecting the appropriate POCT system/assay for decision-making in emergencies. - Methods: Systematic review with PubMed and Cochrane library search for published studies until September 6, 2024. Papers were included if in English, original research using blood samples from DOAC patients and POCT was implemented. Two reviewers assessed studies for eligibility and quality. Data from studies were aggregated and diagnostic accuracy at DOAC plasma thresholds of 30/50/100 ng/ml was recalculated. - Findings: 16 studies involving four commercially available POCT systems/assays were identified. Eleven studies evaluated blood-based POCT and five used urine for indirect estimation of DOAC plasma levels. - Discussion: DOAC Dipsticks do not require knowledge about the taken DOAC, but measure urine and, due to low specificity, require blood testing in case of positive results. Hemochron Signature Elite (HSE) and CoaguChek use global coagulation assays and provide high sensitivity for edoxaban and rivaroxaban, HSE additionally for dabigatran. Due to insufficient correlation, both POCT are not recommended for apixaban, CoaguChek also not for dabigatran. The thromboelastometric ClotPro performs well for all DOAC, does not require knowledge about the DOAC, but was taken off the market recently. - Conclusion: Studies have shown feasibility of POCT in identifying blood samples containing clinically relevant DOAC plasma concentrations. Each POCT device has its own unique limitations. Knowledge about the POCT assays, time since last intake and type of DOAC enhances confidence in making appropriate therapeutic decisions. We propose an algorithm that could help guiding physicians in selecting an appropriate POCT system/assay in DOAC-related emergencies.
Gesehen am 05.11.2025